2005
DOI: 10.1177/000312240507000407
|View full text |Cite
|
Sign up to set email alerts
|

Interorganizational Determinants of Promotion: Client Leadership and the Attainment of Women Attorneys

Abstract: S ince Baron and Bielby's (1980) call to engage more directly the role of organizations in stratification processes, an informative and compelling set of research has improved our understanding of how organizations affect individual attainment (see Kerckhoff 1995 for a review). One of the principal areas of research within this vein has been the mobility of women within organizations (e.g., Baron, Mittman, and Newman 1991;Cohen, Broschak, and Haveman 1998). Through work that has emphasized both individual ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 60 publications
3
109
0
Order By: Relevance
“…These positive spillovers may extend outside the firm. For example, law firms whose key clients have women on their boards are more likely to promote women (Beckman and Phillips, 2005). While the importance of women to corporate boards has been long acknowledged (Burke, 1997;Bilimoria and Wheeler, 2000), females have made only modest gains in terms of directorships on corporate boards (Arken et al, 2004;Daily et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These positive spillovers may extend outside the firm. For example, law firms whose key clients have women on their boards are more likely to promote women (Beckman and Phillips, 2005). While the importance of women to corporate boards has been long acknowledged (Burke, 1997;Bilimoria and Wheeler, 2000), females have made only modest gains in terms of directorships on corporate boards (Arken et al, 2004;Daily et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…-law firms' clients have played a leading role in getting more women promoted to partnerships in the law firms that serve as their outside counsel (Beckman & Phillips 2005); -activist stakeholders have changed the demographic composition of corporate boards of directors (Rose & Bielby 2011, Hillman, Shropshire & Cannella 2007) and other employment practices (David, Bloom & Hillman 2007); -investors' willingness to hold stock has reflected information about employment practices (Richardson & Welker 2001, Wright et al 1995;…”
Section: Empirical Evidence That Information Regulation Workmentioning
confidence: 99%
“…In an earlier study, Kalev and colleagues (2006) also showed that the proportion of white women, black men, and black women in firms increased the most due to programs that established organizational responsibility for diversity. In a study of women partners in law firms, Beckman & Phillips (2005) show that the percentage of female partners in law firms is growing and that this growth is related to the gender diversity of the firms' corporate clients.…”
Section: A Positive For What?mentioning
confidence: 99%